Diagnostic criteria for apathy in neurocognitive disorders. Issue 12 (5th May 2021) - Miller, David S.; Robert, Philippe; Ereshefsky, Larry; Adler, Lawrence; Bateman, Daniel; Cummings, Jeff; DeKosky, Steven T.; Fischer, Corinne E.; Husain, Masud; Ismail, Zahinoor; Jaeger, Judith; Lerner, Alan J.; et al.
Abstract: Introduction: Apathy is common in neurocognitive disorders (NCD) but NCD‐specific diagnostic criteria are needed. Methods: The International Society for CNS Clinical Trials Methodology Apathy Work Group convened an expert group and sought input from academia, health‐care, industry, and regulatory bodies. A modified Delphi methodology was followed, and included an extensive literature review, two surveys, and two meetings at international conferences, culminating in a consensus meeting in 2019. Results: The final criteria reached consensus with more than 80% agreement on all parts and included: limited to people with NCD; symptoms persistent or frequently recurrent over at least 4 weeks, a change from the patient's usual behavior, and including one of the following: diminished initiative, diminished interest, or diminished emotional expression/responsiveness; causing significant functional impairment and not exclusively explained by other etiologies. Discussion: These criteria provide a framework for defining apathy as a unique clinical construct in NCD for diagnosis and further research.